2016
DOI: 10.1016/j.ijepes.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a standstill parameter identification technique for the synchronous generator

Abstract: This work presents the development of an offline standstill estimation technique, where the synchronous machine is locked at an arbitrary (but known) angle and is excited over a short period of time. The proposed time domain method requires few seconds of captured data in contrast to the well-known standard Standstill Frequency Response (SSFR) technique that could take more than 6 hours to conduct. This is based on nonlinear least squares estimation and algebraic elimination theory. The resulting algorithm is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Also, the simulations are carried out in Matlab R2019b, on the operating system Windows 10. The objective function, which is minimized in the BWO and ABWO algorithms, is given in (18).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the simulations are carried out in Matlab R2019b, on the operating system Windows 10. The objective function, which is minimized in the BWO and ABWO algorithms, is given in (18).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Test methods that rely on measuring field and armature voltage and current are proposed in a significant number of recent studies [17]- [26]. Authors have demonstrated the use of a large variety of methods for the determination of the parameters: nonlinear LS is used in [17], [18], while the LS algorithm along with observers for estimation of damper current is applied in [19]- [21], nonlinear mapping is demonstrated in [22], and the use of Hartley series is proposed in [23]. An improved dynamic state estimator called the Unscented Kalman filter (UKF) is used in [24], a univariate search method is applied in [25], and a maximum likelihood algorithm is demonstrated in [26].…”
mentioning
confidence: 99%
“…The error index relates to the squared error in ( 10) and (20). It determines whether the identified parameters provide a good fit for the data, see [32]- [34], and is defined as…”
Section: A Validation Metricsmentioning
confidence: 99%
“…A voltage signal is injected into stator terminals and the transient current responses of armature windings and the field winding are recorded for parameter estimation [11]. In this kind of test, the type of input signal can be flexibly selected, such as DC step signal [10][11][12], DC pulse signal [13], sinc signal [14], and chirp signal [15,16]. Their advantages lie in the safety and short duration at the experimental stage.…”
Section: Introductionmentioning
confidence: 99%
“…Maurer summarized and proposed two arbitrary rotor position parameter identification methods for the DC decay test [18]. Oteafy gave an advanced arbitrary rotor position estimation technique where the stator windings were excited by a threephase chirp signal, his method needed to know the rotor angle in advance [16]. However, in the existing SSTR method literature [10][11][12][13][14][15], the capacity of the prototypes used in their tests was relatively small, it did not involve problems such as the difficulty in rotor positioning or the lack of a matching prime mover.…”
Section: Introductionmentioning
confidence: 99%